IN SEARCH OF THE TRADITIONAL ARCHITECTURAL IDENTITY: THE CASE OF MADINAH, SAUDI ARABIA - Ashour, Randah (Journal of Islamic Architecture, 2020)
Rowshan is the projected latticework window, commonly found in faÃ§ades of traditional dwellings in Madinah. Due to climatic and social functions that Rowshan provides, it achieved widespread popularity in the traditional architecture of Madinah, which gave the city its unique architectural identity. The objective of this research is to explore the professionals' opinions toward the erosion of the traditional architectural identity within contemporary architecture in Madinah, as well as the ensuing decline in the use of Rowshan element that defines this particular style of architecture and ascertaining whether they are interested in reviving Rowshan element in their architectural projects. The method of this research is interviews with 15 professionals who were carried out in Madinah between 1/10/2016 â€“ 1/12/2016. The interview questions were semi-structured, and the data were analyzed using thematic analysis. Overriding opinions concluded that Rowshan's legacy is of great value in Madinah society, and the need to preserve it within contemporary architecture is essential. The respondents' opinions also agreed that ways should be found to develop Rowshan's designs, which would ensure that the form of Rowshan is integrated with its function.